A Study of Flood Disaster Mitigation at the Tambak Anyar Traditional Polder in Banjar Regency South Kalimantan - Novitasari Novitasari; Holdani Kurdi; Efri Sonia Adelia Sonata (Journal of Wetlands Environmental Management, 2021)
The Tambak Anyar polder is one of the many traditional polders scattered in the Banjar Regency. Nevertheless, this polder is flooded almost every year. The purpose of this research is to evaluate dependable discharge that entering to polder system that can be supported by the river capacity inside the polder for flood mitigation. The method used to estimate the water availability is the Mock Model. Furthermore, the data needed are observed discharge, rainfall, and evapotranspiration data. The results of water availability analysis shown that the maximum dependable flow Q80% obtained is 4.89m3/s in the 1st period of January, and the minimum dependable flow Q80% is 1.37 m3/s in the 2nd period of September. The discharge entering the polder is quite large; the capability of Tambak Anyar River as a conveyor channel only can collect 29.74% from the dependable discharge, while the Rantau Bujur River only can accommodate 7.47% in April. In May, Tambak Anyar River's capability can only collect 7.17% from the dependable discharge, while the Rantau Bujur River can only accommodate 0.81%. The amount of discharge cannot be supported by the conveyor river inside the polder. The paddy fields in the Tambak Anyar polder often overflow caused by excess water. This excess of water caused floods that inundated the polder area and the other areas in Banjar Regency as of the beginning of January 2021. The amount of water that has access to the polder is not counterbalanced by watergates facilities and infrastructure management.